STORYTELLING ANALYSIS ON YOUTUBE ACCOUNT CONTENT @NADIAOMARA - Amelia, Nike Firnanda Dwi; Aesthetika, Nur Maghfira (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze Storytelling on the content of @NadiaOmara youtube account. Method: This research also uses Joe Lambert's digital storytelling theory which includes seven main elements. The research method used is a qualitative approach with a descriptive nature, which is carried out through observation of YouTube content @NadiaOmara. The data analysis technique refers to the model developed by Miles and Huberman, which includes three main stages, namely data reduction, data presentation, and conclusion drawing or verification process. Results: The results of the study show that the success of Nadia Omara's storytelling is supported by the use of seven digital storytelling elements by Joe Lambert, namely Point of View, Dramatic Question, Emotional Content, The Gift of Your Voice, the power of the soundtrack, Economy, Pacing which creates a strong story atmosphere and maintains the audience's attention until the end. The narrative techniques applied not only build tension, but also strengthen the emotional connection with the audience. Novelty: By understanding this strategy, this research can be a reference for other content creators who want to develop more effective storytelling on digital platforms.